Perbandingan Undang-Undang Nomor 14 Tahun 1992 tentang Lalu Lintas Dan Angkutan Jalan dengan Rancangan Undang-Undang Republik Indonesia Tentang Lalu Lintas dan Angkutan Jalan - Mailinda Eka Yuniza (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2009)
There are several weaknesses of UU LLAJ. The first weakness is related to centralistic approach used in the UU. Second, the content of the UU has not yet been adjusted with several related new regulations. Third, it has not yet integrate land, marine and air transport. Forth, there are overlaps among related institutions on their rights and responsibilities. Fifth, it has not yet accommodated low-cost and efficient public services. RUU LLAJ, on the other hand, is drafted to elucidate the weaknesses of UU LLAJ. Some changes regulated on RUU LLAJ are regarding decentralization approach, new type of license and new authority on issuing license, and the integration of land, marine and air transport. Furthermore, the RUU LLAJ regulates public participation which has not yet regulated in UU LLAJ. Some of the changes are positive. However, the changes regarding the license system could increase public burden and could cause public confusion.